Braut 3 - Zeeberg, Nils Kristian (Vejhistorie, 2023)
Anmeldelse af Stormbringer, Geir Atle (red.) Braut 3 – Articles from Northern European Road History, Norsk Vegmuseum, Lillehammer, 2017, 138 sider.